Profitability Determinants of Palm Oil Marketing in Umuahia Agricultural Zone of Abia State, Nigeria - Anyanwu, Uchechi Gerarada; Osuji, Emeka Emmanuel; Ben-Chendo, Nkiruka Glory (Finance & Economics Review, 2020)
Purpose: This study aims to ascertain the profitability determinants of palm oil marketing in Umuahia Agricultural Zone of Abia State, Nigeria. Methods: Data on socio-economic characteristics of the respondents, cost, and returns of palm oil marketing in the area were collected using a multi-stage sampling technique from 60 palm oil marketers in Abia State. A descriptive statistical technique, marketing margin, profitability models, and the ordinary least squares multiple regression techniques were used to analyze the data obtained. Results: The empirical analysis showed that palm oil marketers mean age to be 47 years with a household size of 5 persons. 77% of the palm oil marketers were males while only 23% were females. The mean marketing experience of the palm oil marketers was estimated to be 16 years. The gross and net marketing margins were estimated at N55, 288.91, and N54, 076.91 respectively. The marketing margin was found to be ?81,221.22 and profitability was estimated at 0.33. Age, household size, education, and marketing experience were statistically significant at 5% and influenced the profitability of palm oil marketing in the area. Implications: Considering the net profit obtained from palm oil marketing in the area, there is a need to intensify its management and marketing strategies to further harness more profitable outcomes in the future. Also enabling environment should be created to make production and marketing of the product less stressful, especially for women entrepreneurs.